Victim contact work in the probation service. Paradigm shift or Pandora's box - Crawford, Adam (The British journal of criminology, 2001)
The 1990 Victim's Charter created an obligation for the Probation Service in England and Wales to contact the victims, or their families, of life sentence prisoners prior to any consideration of the offender's release to enquire whether they have anxieties about the release. In 1996 this was broadened to include the victims of serious violent or sexual offences'. The implementation of the Victim's Charter requirements has been both hesitant and variable across different Probation Services. This paper considers some of the findings of a study of victim contact work in the Probation Service and their implications, particularly with regard to the views and experiences of victims. The research fieldwork focused on the practice response to the Victim's Charter requirements of two Probation Services, both of which had in place nationally recognized, coherent and yet different models of victim contact service delivery. This paper examines the impact of victim contact work upon victims, the management of offenders and the Probation Service. It explores some of the ambiguities and tensions in translating policy initiatives concerning the needs of victims into the delicate balance of criminal justice